Hambatan Eksekusi Putusan Hakim dalam Perkara Jinayah pada Mahkamah Syar’iyah Bireuen - Muazzin Muazzin (Universitas Syiah Kuala, 2011)
ABSTRACT: The existence and authority Syar'iyah Courts regulated in Qanun Number 10 of 2002 on the Islamic Syari'ah Courts. Since the Year 2007 to Year 2010, the Syar’iyah Court Bireun has examined on jinayah case as many as 27 cases. Although the Court's decision in the case already have permanent legal force, yet one of the case is conducted or executed by the State Attorney Bireun. The results showed that there are some things that cause no or not execution judgement of judge Syar'iyah Court Bireun, Syar'iyah Court Bireun and the State Attorney Bireun have no special budget to carry out additional tasks as implementing agencies in the implementation of Islamic Law in Aceh, Qanun Aceh does not give authority to the institutions of law enforcement to make arrests of suspects, accused and convicted in the case jinayah. The Constraints of Execution on the Conviction of Syariah Law Case Held by Syar’iyah Court Bireuen